(untitled) (Circe de clásicos y modernos, 2023)
This work aims to explore the literary and morphosyntactic particularities of the lullaby present in the Poem of Danae (fr. 271 P.) by Simonides, Nethaulers (fr. 47a R.) by Aeschylus and the Idyll XXIV by Theocritus. The purpose is to demarcate the common characteristics between the songs and to analyze the rhetorical and thematic resources used as a strategy of the poets to characterize the direct speech of certain characters (women and satyrs). It is expected to achive a delimitation of the genre of the lullaby as such and consider its performance context in link with the scarcity of its conservation.